The Influence of Financial Technology Adoption, Digital Financial Literacy, and Data Security on Interest in Using OVO - Januardha, M. Zaky Ayyasy; Cahyono, Tomy Dwi (Al-Qalam Institue, 2025)
The rapid growth of financial technology (fintech) in Indonesia has promoted a shift toward a cashless society, yet adoption remains uneven, particularly in semi-urban areas like Sumbawa Regency. This study examines the influence of Financial Technology Adoption (X1), Digital Financial Literacy (X2), and Data Security (X3) on Interest in Using OVO (Y). Using a quantitative survey method, data were collected from 100 purposively selected OVO users in Sumbawa. Multiple linear regression analysis with SPSS 25 revealed that all three variables—FinTech Adoption (t=3.647), Digital Financial Literacy (t=4.100), and Data Security (t=4.103)—have a positive and significant partial effect on interest in using OVO (Sig. = 0.000 < 0.05). Together, they explain 62.1% of the variance in user interest (Adjusted R² = 0.621). These findings highlight that user interest is shaped not only by technology availability but also by digital literacy and perceived data security. For regions like Sumbawa, accelerating digital financial inclusion requires a holistic approach that combines education, trust-building, and innovation.